RISK FACTORS FOR DEVELOPING PNEUMONIA IN PATIENTS WITH ACUTE LEUKEMIA RECEIVING CHEMOTHERAPY - Phuong, Vu Minh; Linh, Le Khanh; Yen, Duong Hai (Tạp chí Sinh lý học Việt Nam, 2022)
Background: Pneumonia is one of the serious complications during chemotherapy for acute leukemia. The purpose of this study was to determine the incidence rate, clinical characteristics, and risk factors for pneumonia in patients with acute leukemia after chemotherapy. Methods: Two hundred and nine patients with acute myeloid leukemia (AML) and acute lymphoblastic leukemia (ALL) were enrolled in the cohort study, in which 138 patients received chemotherapy, 71 patients had previous pneumonia, so chemotherapy should be delayed. Results: Of the 138 patients who received chemotherapy, 40 patients (29%) developed pneumonia after chemotherapy. Post-chemotherapy pneumonia patients were less likely to have dypsnea, respiratory failure, and severity than those of previous pneumonia patients with P= 0.002, 0.004, and 0.012; respectively. Female patient, non-complete remission (CR) status (include: state of not reaching CR before or previous not received chemotherapy), neutrophil count delay below 0.5 G /L for 7 days, were risk factors for developing pneumonia after chemotherapy with P= 0.036, 0.002 and 0.005; respectively. Conclusions: Pneumonia after chemotherapy for acute leukemia was common. Female patients, non-CR status (include: state of not reaching CR before or previous not received chemotherapy), a delay in neutrophil count below 0.5G /L for 7 days, were high- risk factors of developing pneumonia after chemotherapy.